Enhancing efficacy of gemcitabine in pancreatic patient-derived xenograft mouse models - Andriana Inkoom; Nkafu Ndemazie; Kevin Affram; Taylor Smith; Xue Zhu; Patrick Underwood; Sunil Krishnan; Edward Ofori; Bo Han; Jose Trevino; Edward Agyare (Elsevier, 2020)
Gemcitabine (Gem), a nucleoside analog, is a preferred choice of treatment for pancreatic cancer (PCa) and often used in combination therapy against wide range of solid tumors. It is known to be rapidly inactivated in blood by cytidine deaminase. The objective of the study was to improve the systemic stability and anticancer activity of modified Gem termed 4-N-stearoylGem (4NSG) In this study, the IC50 values of 4NSG treated MiaPaCa-2 and primary pancreatic cancer (PPCL-46) cultures were significantly lower when compared with gemcitabine hydrochloride (GemHCl) treated cultures. In acute toxicity study, liver enzyme level of aspartate aminotransferase (AST) of the control mice was not significantly different from AST levels of 4NSG and GemHCl treated mice. However, alanine aminotransferase (ALT) level of control mice (67 ± 5 mUnits/mL) was significantly lower compared with ALT levels of GemHCl (232 ± 28 mUnits/mL) and that of 4NSG (172 ± 22 mUnits/mL) (p < 0.0001). More importantly, ALT level of 4NSG was lower than ALT level of GemHCl (p < 0.05). Although ALT levels were elevated, pathological images of liver and kidney tissues of control, GemHCl and 4NSG treated mice revealed no architectural changes and no significant change in mice weight was observed during treatment. The bioavailability (AUC) of 4NSG was 3-fold high and significantly inhibited the tumor growth as compared with equivalent dose of GemHCl. Immunohistochemical staining revealed that 4NSG significantly inhibited the expression vascular endothelial growth factor (VEGF) receptor. The study is unique because it established, for the first time, enhanced anticancer activity of 4NSG against pancreatic patient-derived xenograft (PDX) mouse model and PPCL-46 cells compared with Gem. 4SGN enhanced pharmacokinetic profile and improved the therapeutic efficacy of the standard-of-care Gem. Lastly, 4GSN showed a remarkable tumor growth inhibition and revealed significant antiangiogenic activity in 4GSN treated pancreatic PDX tumor.